On optimality conditions for nonsmooth vector problems in normed spaces via generalized Hadamard directional derivatives. (3rd April 2023) - Tinh, Phan Nhat
ABSTRACT: By introducing the concepts of generalized Hadamard directional derivatives, we establish first and second order optimality conditions for nonsmooth vector problems with set constraints in normed spaces. Our results generalize, sharpen and strengthen some recent known ones. Illustrative numerical examples are also given.